Australian Directors' Duties: What Does It Mean to Say They are Public Duties? - Kingsford-Smith, Dimity (Victoria University of Wellington Law Review, 2021)
This article pursues the meaning and effect of what are (in Australia, at least )long-standing public duties of directors. It argues that there has been and continues to be, a slow evolution from an exclusively private character, to a hybrid public and private content in Australian directors’ duties. That duties may be both public and private, does not deny the truth of either of those characters. Instead, using the statutory duty of care in s 180(1) of the Corporations Act, this article analyses the juristic features and public elements that animate the duty and its enforcement sanctions. The cardinal legal and practical question of to whom the public directors’ duties are owed, both to no one in particular and to all the world, rather than only to the company, is also considered.